The impact of appropriate antibiotic prescribing on treatment evaluation parameters - Matthias Adorka; Mitonga Kabwebwe Honoré; Martie Lubbe; Jan Serfontein; Kirk Allen (AOSIS, 2013)
The therapeutic impact of inappropriate prescribing of antibiotics is debatable, particularly in situations where infections are treated empirically with multiply prescribed antibiotics. Prescribers may remain under the illusion that such prescriptions are appropriate on the basis of any observed positive treatment outcomes, even though an antibiotic prescribed in such combination therapy may actually be infective against infecting pathogens. This, inevitably, promotes inappropriate antibiotic prescribing. Prescribers may be motivated to make more conscious attempts to prescribe antibiotics appropriately if it is proven that judicious prescribing of antibiotics has positive impacts on treatment outcomes. The objective of this study was to determine the impact of appropriate prescribing of antibiotics on treatment outcomes, days of patient hospitalization and costs related to antibiotic treatment. Observational data on antibiotic treatment were collected for a onemonth period from case notes of all inpatients (n=307) and outpatients (n=865) at five government and mission hospitals in Lesotho. Prescriptions were classified into categories of appropriateness based on extents to which antibiotics were prescribed according to principles. Treatment success rates, mean days of hospitalization and costs of antibiotic treatments of inpatients treated with specified prescription categories were determined. Appropriate prescribing of antibiotics for inpatients had positive impacts on treatment outcomes, patients' days of hospitalization for infections and costs of antibiotic treatments. In outpatient settings, appropriate prescribing of antibiotics failed to show any significant impact on costs of antibiotics. Appropriate prescribing of antibiotics had a positive impact on patients' recovery and costs of antibiotic treatments in inpatient settings.